Atypical memory B cells from natural malaria infection produced broadly neutralizing antibodies against Plasmodium vivax variants - Kochayoo, Piyawan; Moriyama, Saya; Kotaki, Ryutaro; Thawornpan, Pongsakorn; Malee, Chayapat; Leepiyasakulchai, Chaniya; Ntumngia, Francis Babila; Adams, John H.; Takahashi, Yoshimasa; Chootong, Patchanee (PLoS pathogens, 2025)
Expansion of atypical memory B cells (aMBCs) was demonstrated in malaria-exposed individuals. To date, the generation of P . vivax -specific aMBCs and their function in protective humoral immune responses is unknown. Here, P . vivax Duffy Binding Protein II (PvDBPII) probes were generated to detect the development and durability of specific aMBCs, and to demonstrate the capacity of these cells to produce neutralizing antibodies following natural infections. PvDBPII-specific aMBCs were elicited during malaria illness, and they persisted through the recovery phase of infections. To address biology and function of P . vivax -specific aMBCs in producing protective antibodies, a single MBC was cultured, and the secreted IgG was tested for binding and inhibition activity. The aMBC-derived clones produced antibodies with variable levels of anti-PvDBPII IgG in cultures, and some produced high antibody levels comparable to classical MBC clones. Thus, we focused our attention on the function of aMBCs in producing neutralizing antibodies. Among the aMBC clones, A1F12 and B4E11 produced broadly neutralizing antibodies against a panel of PvDBPII variants. Notably, B cell receptors (BCRs) of PvDBPII-specific aMBCs expressed unique IGHV genes, with similar usage of IGHV1-3, comparable to classical MBCs. The somatic hypermutation (SHM) rate and CDR3 length of VH and Vκ in these two MBC subsets were not significantly different. Together, our findings revealed that P . vivax infections elicited the development and persistence of P . vivax -specific aMBCs. The accumulation of aMBCs during and following infections might play an important role in producing protective antibodies against malaria.